A CLINICAL STUDY TO EVALUATE THE EFFICACY OF PANASA PATRA SWEDA AS POORVA KARMA FOR NASYA IN ARDITA W.S.R TO FACIAL PALSY - M. S, *Seetharamu; Goud, Kiran M; D M, Shreyas (International Journal of Ayurveda and Pharma Research, 2019)
Arditha is explained as one among the Vatananathmaja vyadhi by Acharya Charaka. Acharya sushrutha has considered as only Mukha ardha while Acharya Charaka has included Sharira ardha in Arditha.Facial nerve paralysis is the condition which presents with the deviation of half of the face and associated with the impairment of motor and sensory functions of the affected side of the face. Facial paralysis can be placed under the wide spectrum of Arditha vyadhi. In recent years, life time prevalence is about 6.4 to 20 per 1000, which increases with age, and predominantly seen in Females. Contemporary science adopts the treatment wherein chances of reoccurrence are possible. Both Acharya Charaka and Sushrutha as mentioned Nasya and Swedana as the prime line of treatment modalities in Ardita. Aims and objectives of the present study is to evaluate the efficacy of Panasa patra sweda followed by Nasya karma in Ardita. 10 patients fulfilling the inclusion and exclusion criteria were selected for Panasa patra sweda as Poorva karma and Nasya for 7 days with Ksheera bala taila 101. It was observed that Maximum patient in the study given statistically significant relief in almost all Parameters. The results of the present clinical study has given (p<0.001) which shown statistically highly significant.